2008
DOI: 10.2172/932944
|View full text |Cite
|
Sign up to set email alerts
|

Crack growth rates and fracture toughness of irradiated austenitic stainless steels in BWR environments.

Abstract: In light water reactors, austenitic stainless steels (SSs) are used extensively as structural alloys in reactor core internal components because of their high strength, ductility, and fracture toughness. However, exposure to high levels of neutron irradiation for extended periods degrades the fracture properties of these steels by changing the material microstructure (e.g., radiation hardening) and microchemistry (e.g., radiation-induced segregation). Experimental data are presented on the fracture toughness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
0
21
0
2
Order By: Relevance
“…As discussed above, the aging embrittlement depends on many materials and environmental parameters, including chemistry, processing condition, aging temperature, and irradiation condition. [1][2][3][4][5][6][7][37][38][39][40] Practically, the wide range of impact energy data influenced by the parameters mentioned above may not allow an integration into single figure in a discernible way. Instead, a schematic illustration was constructed to express a summary of the reviewed context above: Fig.…”
Section: Mechanism Of Thermal Embrittlement and Influential Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, the aging embrittlement depends on many materials and environmental parameters, including chemistry, processing condition, aging temperature, and irradiation condition. [1][2][3][4][5][6][7][37][38][39][40] Practically, the wide range of impact energy data influenced by the parameters mentioned above may not allow an integration into single figure in a discernible way. Instead, a schematic illustration was constructed to express a summary of the reviewed context above: Fig.…”
Section: Mechanism Of Thermal Embrittlement and Influential Factorsmentioning
confidence: 99%
“…It is also well known that thermal aging has a synergistic effect with irradiation when the CASS components are used in or near a reactor. [37][38][39][40] The effect is included in Fig. 3 although no detailed discussion is provided in this article.…”
Section: Mechanism Of Thermal Embrittlement and Influential Factorsmentioning
confidence: 99%
“…Figure 46 shows the estimated fracture toughness values obtained in this study along with the unirradiated fracture toughness values of 304 and 316 SSs reported by Mills 30,31 and some previous results from Halden-I and -II irradiated specimens. 15,26 Despite a difference in test temperature, a decreasing trend can be seen with increasing dose for this group of data. Among the samples tested in the current study, SA 304L shows the best fracture resistance, and the measured J at 0.2-mm offset line was about 95 kJ/m 2 .…”
Section: Irradiation Embrittlementmentioning
confidence: 67%
“…This strong effect of PPU was different from that observed at lower doses and in BWR NWC (a high-corrosionpotential environment). 15 Periodic partial unloading seemed not to have a substantial effect on the measured CGRs in high-purity water with 700-800 ppb DO for irradiated SSs. 15 The different sensitivity to partial unloading suggests a combined effect of SCC and low-cycle fatigue on the crack growth response of irradiated SSs in the low-corrosion-potential environments.…”
Section: Effect Of Ppumentioning
confidence: 85%
See 1 more Smart Citation